Phenotypic and Genetic Heterogeneity in Vibrio cholerae O139 Isolated from Cholera Cases in Delhi, India during 2001–2006 - Ghosh, Raikamal; Sharma, Naresh C.; Halder, Kalpataru; Bhadra, Rupak K.; Chowdhury, Goutam; Pazhani, Gururaja P.; Shinoda, Sumio; Mukhopadhyay, Asish K.; Nair, G. Balakrish; Ramamurthy, Thadavarayan (Frontiers in Microbiology, 2016)
Incidence of epidemic Vibrio cholerae serogroup O139 has declined in cholera endemic countries. However, sporadic cholera caused by V. cholerae O139 with notable genetic changes is still reported from many regions. In the present study, 42 V. cholerae O139 strains isolated from 2001 to 2006 in Delhi, India, were retrospectively analyzed to understand their phenotype and molecular characteristics. The majority of isolates were resistant to ampicillin, furazolidone and nalidixic acid. Though the integrative conjugative element was detected in all the O139 isolates, the 2004-2006 isolates remained susceptible to co-trimoxazole, chloramphenicol, and streptomycin. Cholera toxin genotype 1 was present in the majority of the O139 isolates while few had type 3 or a novel type 4. In the cholera toxin encoding gene (ctx) restriction fragment length polymorphism, the majority of the isolates harbored three copies of CTX element, of which one was truncated. In this study, the ctx was detected for the first time in the small chromosome of V. cholerae O139 and one isolate harbored 5 copies of CTX element, of which 3 were truncated. The ribotype BII pattern was found in most of the O139 isolates. Three V. cholerae O139 isolated in 2001 had a new ribotype BVIII. Pulsed-field gel electrophoresis analysis revealed clonal variation in 2001 isolates compared to the 2004-2006 isolates. Molecular changes in V. cholerae O139 have to be closely monitored as this information may help in understanding the changing genetic features of this pathogen in relation to the epidemiology of cholera.